EFFECTS OF A WILD GREEN OAT EXTRACT ON MENTAL PERFORMANCE: A HUMAN CLINICAL STUDY USING SOURCE DENSITY ANALYSIS OF THE HUMAN EEG - Aydogan, C.; Schellekens, C.; Wullschleger, C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Preparations from green oat have traditionally been used to support mental health and cognitive function [1, 2]. The patented wild green oat extract NeuravenaÂ® has been shown to support learning, increase alertness, have stress coping and stimulating abilities and to influence brain activity in-vivo [3,4]. Underlying study is a randomized, double-blind, placebo-controlled cross-over clinical trial to confirm NeuravenaÂ®’s effects on mental fitness and performance under pressured situations, using source density analysis of the EEG [5] in human volunteers. Twenty healthy men and women ingested one single dose of 2500 mg NeuravenaÂ®, or placebo, at start of the trial. Brain activity signals were recorded during 4 hours under relaxed and pressured conditions, using a standardized set of electrodes. NeuravenaÂ® was found to change the basic brain activity through a significant decrease of frontal and temporal delta and theta waves as well as an increase in alpha2 wave activity. Changes in evoked short term brain activity during the performance of the concentration stress test showed that NeuravenaÂ® significantly increases delta and theta wave activity in the brain regions closely connected to mental performance. The abovementioned changes confirm the positive effects of NeuravenaÂ® on cognitive function and are in line with the extract mediating stimulating properties. The intake of NeuravenaÂ® helps increase overall mental fitness in an individual’s daily life. Moreover, it has been shown to help improve cognitive function (concentration, learning, alertness) under pressure.